Peningkatan Kualitas Penyusunan RPPH Melalui Monitoring Dan Evaluasi Pelaksanaan Program Sekolah Oleh Pengawas TK Di Kabupaten Pasaman Barat - Sri Utami, S.Pd (JURNAL MANAJEMEN PENDIDIKAN, 2016)
AbstrakBased on the observations that have been researchers did teachers in kindergarten West Pasaman, it was found that the ability of teachers to prepare RPPH still low. The purpose of this study is to describe and obtain information about the preparation of RPPH In kindergarten Barat.Penelitian Pasaman of a school action research. The procedure in this research include planning, action, observation and reflection. The study consisted of two cycles of the four meetings. Subjects consisted of 40 kindergarten teachers West Pasaman which consists of 11 schools. Data were collected by using observation sheet. Data were analyzed using percentages. The results showed that the Monitoring and Evaluation Can Improve teacher preparation RPPH In kindergarten Pasaman of Barat.Hal is evidenced by the evavaluasi and monitoring may Improving the quality of teacher preparation RPPH In kindergarten West Pasaman from the first cycle to the second cycle. The average teacher's ability to improve manufacturing of RPPH in the first cycle was 50.97 with less category, the second cycle is 74.35 with the category Fairly and the third cycle is 83.35 Good.Keywords: Monitoring and Evaluation, Preparation RPPH